1978
DOI: 10.1007/bf01330901
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled DNA-synthesis in UV-irradiated spleen lymphocytes of the rat after whole-body X-irradiation

Abstract: Unscheduled DNA-synthesis of UV-irradiated spleen lymphocytes of the rat is inhibited in a dose-dependent manner by total-body X-irradiation. The reaction is observed immediately after exposure and reaches its maximum within 8--16 h. Doses of some rads are detectable. Following sublethal X-irradiation (250 rad), regeneration takes 4--6 weeks. Analogous results have been obtained in rats treated with 2,4,6-triethyleneimino-1,3,5-triazine. Regardless of the action mechanisms, it is concluded from the present res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
1
1
0
2
Order By: Relevance
“…However, several experiments also yielded a reduced level of UVlight-induced UDS in adapted cells, implying that the differences are rather a result of a variability inherent to this endpoint, than of some induced cellular processes. Similar variabilities of UV-light-induced UDS levels have also been reported by others (Hollatz and Tempel 1978;Cleaver and Thomas 1981).…”
Section: Discussionsupporting
confidence: 73%
“…However, several experiments also yielded a reduced level of UVlight-induced UDS in adapted cells, implying that the differences are rather a result of a variability inherent to this endpoint, than of some induced cellular processes. Similar variabilities of UV-light-induced UDS levels have also been reported by others (Hollatz and Tempel 1978;Cleaver and Thomas 1981).…”
Section: Discussionsupporting
confidence: 73%
“…It may be suggested that these events represent an intense DNA-repair replication. However, the magnitude of this process, which can be detected easily by 3H-thymidine labeling, is rather surprising if we compare the Recovery from irradiation injury after 12 h Only partly recovery from irradiation injury after 8-12 h underlying replication intensity with other reports on the same subject (Yoshizawa et al 1978;Tempel 1979;Hollatz and Tempel 1978). These observations lead to the question of the underlying principles leading to this topological reparation diversity.…”
Section: Discussionmentioning
confidence: 69%
“…Он составляет 62 % после 10 мин инкубации и достигает 83 % спустя 1 ч после ее начала. Следовательно, наши ре-зультаты, как и данные литературы [11,12], свидетельствуют о том, что в лимфоцитах, находящихся в стадии Go, после воздействия ионизирующей радиации осуществляется репаративный синтез ДНК, который как этап эксцизионной репарации, по-видимому, соответствует (в свете наших вышеизложенных представлений) фазе первоначального восстановления суперспиральной структуры нуклеоида в этих клетках.…”
Section: в и ващенко л в щедрина в е комарunclassified